Distribution of Symbiotic Genotypes in Rhizobium leguminosarum biovar viciae Populations Isolated Directly from Soils - Louvrier, P. (1996)
The distribution of symbiotic (Sym) plasmid types across background genotypes was investigated in two field populations of Rhizobium leguminosarum biovar viciae isolated directly from soils. PCR-based methods were used to characterize the background genotypes and the Sym gene types. Identical Sym gene types were associated with a variable range of background genotypes, while the same background genotype could harbor distinct Sym gene types. Random distributions of Sym gene types in the background genotypes were observed in the two soil populations. These results suggest that Sym plasmid transfer is less restricted than previously thought on the basis of the analysis of strains isolated from legume nodules.